KONTRIBUSI METODOLOGIS MUHAMMAD ABED AL-JABIRI DALAM STUDI ISLAM (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2017)
Muhammad Abed al-Jabiri is a figure of one of the Muslim philosophers living in the modern-contemporary era, al-Jabiri mindset or style of thinking is similar to other modern paradigms such as M.Arkoun who deconstructs to understand the true nature of the text. Muhammad Al Abid Al -Jabiri tries to offer new approaches to Islamic studies. As in his book Naqd al-'Aql al-'Aroby (Arabic reasoning), Takwin al-'Aql al-'Aroby (Arabic logic formation), Bunyah al-'Aql al 'Aroby (Arabic logical structure), critically offered New and simultaneous methods of criticism of old-fashioned Arabic epistymology. The offer displayed by al-Jabiri is to categorize these patterns of thought (dialectical), burhani (demontrative) and 'irfani (gnosis). The first approach is the naqli (traditional) model, the two models of the aqli (rational) approach, and the three kasyf (mystical) models. Old model approaches are thought to cause new problems. Therefore, inevitably changing the paradigm of thought is a necessity. And al-Jabiri provides answers with three models of thinking above which will provide answers to the problems that moncul in today's modern era.